GAMBARAN PERILAKU POLA MAKAN TIDAK TERATUR PDA MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Amalia Safitri; Angelica Tania; Delviana Lufvita Sari Purba; Indi Rahmawati; Putri Rahmasari; Dhidy Has Idiano; Zuhrina Aidha (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Food is one of the primary needs that must be met to maintain a healthy body. However, irregular eating patterns have become a serious health problem among students. This study aims to analyze eating patterns, food preferences, and nutritional understanding of UIN Sumatera Utara students. Using a qualitative method with a phenomenological approach, this study involved 3 respondents, namely UIN Sumatera Utara students. The results of the study showed that students' eating frequency tends to be irregular, with a tendency to skip breakfast and eat more often twice a day during active college days. Consumption of snacks and fast food is quite high, driven by efficiency factors, time constraints, and the influence of the environment and peers. Most informants prefer heavy and processed foods such as instant noodles, geprek chicken, and ultra-processed snacks, with limited knowledge of balanced nutrition and inconsistent application. The conclusion of this study is that the eating patterns of students in this interview show a tendency to be irregular and unbalanced. Fast food and processed foods are the main choices because they are practical, affordable, and easily accessible, while consumption of fruits and vegetables is very low.